Numeracy Training: Applying Jarimatika Method in Elementary School Students of Border Area Nunpene East Nusa Tenggara - Lailin Hijriani; Meiva Marthaulina Lestari Siahaan; Justin Eduardo Simarmata; Yeni Missa; Margarita Tampani; Nelciana Talan (Smart Society, 2022)
The numeracy skill of elementary school students in border area Nunpene East Nusa Tenggara is still relatively low. This is caused by the students’ habit use counting aid such as calculators. Therefore, it is necessary to have a Lecturer activity in the community to help elementary school students which aim to improve their numeracy skills. Because mathematics teaches various skills, one of which is counting. So that the ability to count is a fundamental thing that must be mastered by students when they learn mathematics. One of learning method that can be done to improve students' numeracy skills is by applying the Jarimatika method which involves the students' own organs directly. Indirectly cognitive and psychomotor abilities will develop simultaneously so as to increase the efficiency of students' counting speed. As for the steps of the service, the method are including the introduction of the counting method, assistance during the learning process, then providing an evaluation. The results of this training are that after the training, it can be seen from the posttest results that students have increased their numeracy skills using the Jarimatika method. As well as increasing the knowledge of mathematics teachers regarding the use of the Jarimatika method as an alternative method of numeracy